Urological men's health : A guide for urologists and primary care physicians - Shoskes, Daniel A. (Current Clinical Urology, 2012)
Urological Men's Health: A Guide for Urologists and Primary Care Physicians covers the major urologic conditions that have an impact on the health and well being of the adult male. It opens with an overview of general men's preventative health, as practiced by a world leading Executive Health center. The volume covers the major genitourinary malignancies and addresses the latest controversies in screening and treatment selection. This is followed by coverage of the conditions that don't shorten life but have major impact on quality of life and health care expenditure: BPH, urinary incontinence, infertility, urethral strictures, erectile dysfunction, urinary tract infections and chronic pelvic pain. Also included are chapters on herbal and complementary therapy, psychological and spousal support in urologic illness and the links between genitourinary disease and general vascular endothelial dysfunction. Urological Men's Health: A Guide for Urologists and Primary Care Physicians will be of great value to Urologists, Internists, General Practitioners and the residents and fellows who train within these specialties.